Regnase-1 and Roquin Nonredundantly Regulate Th1 Differentiation Causing Cardiac Inflammation and Fibrosis - Cui, Xiaotong; Mino, Takashi; Yoshinaga, Masanori; Nakatsuka, Yoshinari; Hia, Fabian; Yamasoba, Daichi; Tsujimura, Tohru; Tomonaga, Keizo; Suzuki, Yutaka; Uehata, Takuya; Takeuchi, Osamu (The Journal of immunology (1950), 2017)
Regnase-1 and Roquin are RNA binding proteins that are essential for degradation of inflammatory mRNAs and maintenance of immune homeostasis. Although deficiency of either of the proteins leads to enhanced T cell activation, their functional relationship in T cells has yet to be clarified because of lethality upon mutation of both Regnase-1 and Roquin. By using a Regnase-1 conditional allele, we show that mutations of both Regnase-1 and Roquin in T cells leads to massive lymphocyte activation. In contrast, mutation of either Regnase-1 or Roquin affected T cell activation to a lesser extent than the double mutation, indicating that Regnase-1 and Roquin function nonredundantly in T cells. Interestingly, Regnase-1 and Roquin double-mutant mice suffered from severe inflammation and early formation of fibrosis, especially in the heart, along with the increased expression of Ifng, but not Il4 or Il17a. Consistently, mutation of both Regnase-1 and Roquin leads to a huge increase in the Th1, but not the Th2 or Th17, population in spleens compared with T cells with a single Regnase-1 or Roquin deficiency. Regnase-1 and Roquin are capable of repressing the expression of a group of mRNAs encoding factors involved in Th1 differentiation, such as Furin and Il12rb1, via their 3′ untranslated regions. Moreover, Regnase-1 is capable of repressing Roquin mRNA. This cross-regulation may contribute to the synergistic control of T cell activation/polarization. Collectively, our results demonstrate that Regnase-1 and Roquin maintain T cell immune homeostasis and regulate Th1 polarization synergistically.